2020
DOI: 10.26434/chemrxiv.12333314.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Boron-Doped Boron Nitride Photocatalyst for Visible Light-Driven H2 Evolution and CO2 Photoreduction

Abstract: <p>Developing robust, multifunctional photocatalysts that can facilitate both hydrogen evolution <i>via</i> photoreforming of water and gas phase CO<sub>2</sub> photoreduction is highly desirable with the long-term vision of integrated photocatalytic setups. Here, we present a step-change in the family of boron oxynitride materials by introducing the first example of a B-doped boron oxynitride (B-BNO). This material resolves an on-going bottleneck associated with BN-based material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The high resolution O 1s core level spectrum and atomic composition for the representative BNO sample is shown in Figures 2b and 2c, respectively. The peak centred at 533.1 eV in Figure 2b is attributed to boron oxynitride (B−O x −N 3‐x ) species, which stems from the in‐plane substitution of oxygen atoms in the BN lattice, as we have described in a prior studies [9,10] . The analysis indicates a significant proportion of oxygen (10.6±0.6 at.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…The high resolution O 1s core level spectrum and atomic composition for the representative BNO sample is shown in Figures 2b and 2c, respectively. The peak centred at 533.1 eV in Figure 2b is attributed to boron oxynitride (B−O x −N 3‐x ) species, which stems from the in‐plane substitution of oxygen atoms in the BN lattice, as we have described in a prior studies [9,10] . The analysis indicates a significant proportion of oxygen (10.6±0.6 at.…”
Section: Resultsmentioning
confidence: 53%
“…The presence of the boron oxynitride (B−O x −N 3‐x ) species observed in Figure 2b can give rise to the formation of isolated OB 3 sites. In a previous study, [9] we showed that these isolated OB 3 sites induce a paramagnetic radical signal through the introduction of an unpaired electron from the incoming oxygen atom to the system, which contributes to band gap narrowing. The paramagnetic signature of the BNO species, measured using X‐band electron paramagnetic resonance (EPR) spectroscopy under ambient conditions, is shown in Figure 3a (inset).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations